2020
DOI: 10.3892/etm.2020.8839
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 protects articular cartilage by inhibiting the Wnt/β‑catenin signaling pathway

Abstract: Low expression levels of 25-hydroxyvitamin D (vitamin D3) in the blood have been reported to be associated with the progression of osteoarthritis; however, the mechanisms by which this occurs remain unclear. The present study aimed to determine the effects of vitamin D3 on chondrocytes. MTT assays were used to determine whether vitamin D3 affects chondrocytes viability. Primary chondrocytes were treated with control culture medium, vitamin D3, tumor necrosis factor (TNF)-α, TNF-α + PNU-74654 [Wingless-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Wnt-βcatenin is also likely to participate in the relationship between osteoblasts and cholesterol [ 27 ]. Recent evidence has shown that cholesterol modulates Xenopus development via the Wnt–β-catenin pathway, while Wnt-βcatenin plays important role in embryonic skeletal development and regulating articular cartilage, synovium, and osteoblasts in adults [ 28 ]. The proper orchestration of both these signaling pathways with lipids and cholesterol is critical for bone production.…”
Section: The Role Of Cholesterol and The Lipid Metabolism In Bone Micro-environmentmentioning
confidence: 99%
“…Wnt-βcatenin is also likely to participate in the relationship between osteoblasts and cholesterol [ 27 ]. Recent evidence has shown that cholesterol modulates Xenopus development via the Wnt–β-catenin pathway, while Wnt-βcatenin plays important role in embryonic skeletal development and regulating articular cartilage, synovium, and osteoblasts in adults [ 28 ]. The proper orchestration of both these signaling pathways with lipids and cholesterol is critical for bone production.…”
Section: The Role Of Cholesterol and The Lipid Metabolism In Bone Micro-environmentmentioning
confidence: 99%